Screening and selection of Brachiaria brizantha accessions for forage values under irrigation at Wondo Genet, Sidama, Ethiopia - Aman Getiso; Diribi Mijena; Edao Shanku (Open Journal of Biological Sciences - Peertechz Publications, 2022)
The experiment was conducted to evaluate different Brachiaria brizantha accessions at the Wondo genet agricultural research center to identify species/accessions so as to use the better performing ecotype for wider distribution among livestock producer communities in the country. Seven Brachiaria grass accessions (B. brizantha, 13151; B. brizantha, 13368; B. brizantha, 13653; B. brizantha, 16550; B. humidicola, 9222; B. brizantha, 13379 and B. mutica,) were used as treatments in randomized complete block design with three replications. The overall dry matter yield for B. humidicola, 9222 (5.95t/ha), and B. mutica, (5.61t/ha) accessions didn't show a significant difference (p > 0.05) but significantly (p < 0.05) lower than all other accessions. Mean plant heights for the accessions were significantly different (p < 0.05) throughout the harvesting cycle period and overall yield with a lower plant height of B. mutica (63.2 cm) while non-significant (p > 0.05) overall mean height was recorded among other accessions. B. brizantha, 13151; B. brizantha, 13368; B. brizantha, 13653; B. brizantha, 16550 and B. brizantha, 13379 accessions outperformed in terms of overall dry matter yield. Further studies on agronomic performances of promising B. brizantha accessions under on-farm conditions and nutritional evaluation involving live-animal experiments are recommended.